2020
DOI: 10.1039/d0ra08718a
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Co-doped with Zr and Ag shows highly efficient visible light photocatalytic behavior suitable for treatment of polluted water

Abstract: The objective of this study is to analyze the effects of zirconium (Zr) and silver (Ag) doping on the photoactivity of titania (TiO2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Several methods have been used by researchers to synthesize TiO 2 nanoparticles such as chemical precipitation [7], combustion [8], sol-gel [9,10], and hydrothermal methods [11]. Among these methods, the sol-gel method is a simple process to synthesis TiO 2 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been used by researchers to synthesize TiO 2 nanoparticles such as chemical precipitation [7], combustion [8], sol-gel [9,10], and hydrothermal methods [11]. Among these methods, the sol-gel method is a simple process to synthesis TiO 2 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite all these benefits, as TiO 2 has a wide band gap (3.2 eV), its photocatalytic efficiency is less in removing pollutants under different light sources. Therefore, to enhance the photocatalytic activity of TiO 2 , researchers employed different processes like metal doping such as Ag, Mn, Cu, V, Mo, Cr, Fe, and Zn and non-metal doping such as P, C, N, S, and TiO 2 nanocomposites . Numerous studies have found that doping metal oxides with transition metals can improve the photocatalytic activity, owing to a shift in the absorption region from UV to visible light due to a change in their electronic structure .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the introduction of codopants (Mn and Co) into TiO 2 promoted the enhancement of its photocatalytic performance due to a displacement of the bandgap energy . Meanwhile, the light absorption of the Zr–Ag codoping TiO 2 catalyst has been extended into the visible light region, making it more effective in eliminating ∼93% of methylene blue for 90 min …”
Section: Introductionmentioning
confidence: 99%